Rare Drosha splice variants are deficient in MicroRNA processing but do not affect general MicroRNA expression in cancer cells - Grund, Stefanie; Polycarpou-Schwarz, Maria; Luo, Chonglin; Eichmüller, Stefan B.; Diederichs, Sven (Neoplasia, 2012)
Drosha is a key enzyme in microRNA biogenesis, generating the precursor miRNA (pre-miRNA) by excising the stem-loop embedded in the primary transcripts (pri-miRNA). The specificity for the pri-miRNAs and determination of the cleavage site are provided by its binding partner DGCR8, which is necessary for efficient processing. The crucial Drosha domains for pri-miRNA cleavage are the middle part, the two enzymatic RNase III domains (RIIID), and the dsRNA binding domain (dsRBD) in the C-terminus. Here, we identify alternatively spliced transcripts in human melanoma and NT2 cell lines, encoding C-terminally truncated Drosha proteins lacking part of the RIIIDb and the entire dsRBD. Proteins generated from these alternative splice variants fail to bind to DGCR8 but still interact with Ewing sarcoma protein (EWS). In vitro as well as in vivo, the Drosha splice variants are deficient in pri-miRNA processing. However, the aberrant transcripts in melanoma cells do not consistently reduce mature miRNA levels compared with melanoma cell lines lacking those splice variants, possibly owing to their limited abundance. Our findings show that alternative processing-deficient Drosha splice variants exist in melanoma cells. In elevated amounts, these alternatively spliced transcripts could provide one potential mechanism accounting for the deregulation of miRNAs in cancer cells. On the basis of our results, the search for alternative inactive splice variants might be fruitful in different tumor entities to unravel the molecular basis of the previously observed decreased microRNA processing efficiency in cancer.
Gesehen am 28.06.2017